1979
DOI: 10.1039/f29797500017
|View full text |Cite
|
Sign up to set email alerts
|

Inelastic electron tunnelling spectroscopy (IETS) of carboxylic acids and related systems chemisorbed on plasma-grown aluminium oxide. Part 1.—Formic acid (HCOOH and DCOOD), acetic acid (CH3COOH, CH3COOD and CD3COOD), trifluoroacetic acid, acetic anhydride, acetaldehyde and acetylchloride

Abstract: A study of the inelastic electron tumelhg spectra GETS) of formic acid, [2H2]formic acid, acetic acid, [2H4]acetic acid and trifiuoroacetic acid shows that these chemisorb from the vapour phase on to plasma-grown aluminium oxide as surface-bound formates and acetates. Detailed vibrational mode band assignments are made and the carboxylates are deduced to be adsorbed symmetrically on, though not necessarily perpendicular to, the oxide surface. The plasma-grown oxide shows enhanced reactivity to acetaldehyde ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

1982
1982
2001
2001

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(31 citation statements)
references
References 0 publications
6
25
0
Order By: Relevance
“…Hence, the different rates of oxidation may suggest that the water plasma is able to establish more readily the equilibrium concentration of water required for rapid oxide growth. The formation of a thermodynamically stable film requiring a certain hydroxyl ion concentration is supported by Brown et al,3 who indicated that stable oxide films could be produced only with trace quantities of water present in the plasma gas.…”
Section: The Influence Of Watermentioning
confidence: 91%
See 2 more Smart Citations
“…Hence, the different rates of oxidation may suggest that the water plasma is able to establish more readily the equilibrium concentration of water required for rapid oxide growth. The formation of a thermodynamically stable film requiring a certain hydroxyl ion concentration is supported by Brown et al,3 who indicated that stable oxide films could be produced only with trace quantities of water present in the plasma gas.…”
Section: The Influence Of Watermentioning
confidence: 91%
“…6 The plasma film was reported to be similar to alumina, 7 which contained hydroxide when the aluminium substrate was maintained at temperatures below 150°C. 1,3,8 Evidence suggested that the oxide crystallinity increased with temperature. Mechanistic studies indicated that oxygen anions may have played a role in the oxidation process.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…2B) and eluted from the gel. DNA fragments labeled at 5'-terminus and bound to peptides (D l-D5) were subjected to A + G reaction of sequencing protocol [17]. The idea is that the sequencing ladder must tively.…”
Section: Resultsmentioning
confidence: 99%
“…DNA was degraded to pyrimidine sequences [13]. The released pyrimidine fragments were separated according to chain length (isopliths) and base composition by thin-layer chromatography on DEAEcellulose (Reanal, Hungary) [14].…”
Section: Methodsmentioning
confidence: 99%